KOMPETENSI GURU DAN BUDAYA ORGANISASI UNTUK MENINGKATKAN KEUNGGULAN BERSAING SEKOLAH PADA MTs. NEGERI PANGKALPINANG - Reniati Reniati; Dedy Dedy (Fakultas Ekonomi Universitas Bangka Belitung, 2015)
The objective of this research is to investigate the influence of teachers’ competence quality. The respondent of the research was 44 teachers of MTs. Negeri Pangkalpinang and 31 students of MTs.Negeri Pangkalpinang. To test all three hypotheses, the researcher used double linear regression of Statistical Product and Service Solution (SPSS) 17.00.Data analysis done using descriptive analysis and statistical analysis (correlation, coefficient of determination, t test, F test and regression). Based on descriptive analysis is know that the teacher’s competence, organizational culture and the school’s competitive quality in the MTs. Negeri of Pangkalpinang quite good. Meanwhile, the results of statistical analysis in mind that the teacher’s competence is very significant effect on the school’s competitive quality. The relationship between the teacher’s competence and school’s competitive quality factor’s are close (strong). Positive and direction, with a correlation coefficient value of 0,954. Organizational cu;lture is very significant effect on the school’s competitive quality. The relationship between organizational culture and school’s competitive quality faktor’s are close (strong). Positive and direction of the correlation coefficient value of 0,853. The result shows that the teachers’ competence and organisational culture influences the school’s competence quality, partially and simultaneously. Teacher’s competence and organizational culture factor’s together can explain the change in school’s competitive quality of 61,20%.